A Brief Review of Para-xylene Oxidation to Terephthalic Acid As a Model of Primary C-H bond Activation - Nor Aqilah, Mohd Fadzil; Mohd Hasbi, Ab. Rahim; Gaanty Pragas, Maniam (Elsevier Ltd, 2014)
The oxidation of para-xylene to terephthalic acid has been commercialised as the AMOCO process (Co/Mn/Br) that uses a homogeneous catalyst of cobalt and manganese together with a corrosive bromide compound as a promoter. This process is conducted in acidic medium at a high temperature (175–225°C). Concerns over environmental and safety issues have driven studies to find milder oxidation reactions of para-xylene. This review discussed past and current progress in the oxidation of para-xylene process. The discussion concentrates on the approach of green chemistry including (1)using heterogeneous catalysts with promising high selectivity and mild reaction condition, (2) application of carbon dioxide as a co‐oxidant, and (3) application of alternative promoters. The optimisation of para-xylene oxidation was also outlined.